Connaissance Ignorance Mystère. L'educazione, apprendre à vivre - Pierluigi Malavasi (Firenze University Press, 2021)
For an education to be more open and inclusive, there is a need for places of experimentation and thoughts. This education shall be capable of patient listening, constructive dialogue and mutual understanding. Edgar Morin has given life, through a fruitful reflective work, to a "field" of theoretical confrontation whose complexity includes a considerable attention towards the science of education. Education is marked by a triptych of knowledge, ignorance and mystery, these are both intertwined in and emblematic of the community of destiny of all humanity. Education is a yearning, a condition and provides consciousness about Homeland Earth for an authentic human development. A path to learn how to live, facing uncertainties and contradictions.